Lateral Decubitus Digital Subtraction Myelography: Tips, Tricks, and Pitfalls - Kim, D.K.; Brinjikji, W.; Morris, P.P.; Diehn, F.E.; Lehman, V.T.; Liebo, G.B.; Morris, J.M.; Verdoorn, J.T.; Cutsforth-Gregory, J.K.; Farb, R.I.; Benson, J.C; Carr, C.M. (American Journal of Neuroradiology, 2020)
SUMMARY: Digital subtraction myelography is a valuable diagnostic technique to detect the exact location of CSF leaks in the spine to facilitate appropriate diagnosis and treatment of spontaneous spinal CSF leaks. Digital subtraction myelography is an excellent diagnostic tool for assessment of various types of CSF leaks, and lateral decubitus digital subtraction myelography is increasingly being used to diagnose CSF-venous fistulas. Lateral decubitus digital subtraction myelography differs from typical CT and fluoroscopy-guided myelograms in many ways, including equipment, supplies, and injection and image-acquisition techniques. Operators should be familiar with techniques, common pitfalls, and artifacts to improve diagnostic yield and prevent nondiagnostic examinations.DSMdigital subtraction myelographySIHspontaneous intracranial hypotensionSSCSFLspontaneous spinal CSF leak